2013
DOI: 10.3109/0142159x.2013.802297
|View full text |Cite
|
Sign up to set email alerts
|

International and American medical graduates in a U.S. pediatric residency program: A qualitative study about challenges during post-graduate year 1

Abstract: The work-related and adjustment challenges that IMGs and AMGs confronted during PGY-1 suggest that the culture of residency socializes IMGs and AMGs regarding professional expectations and responsibilities. Increased awareness of this socialization process among residency program directors, and interventions based on concrete recommendations, can help enhance PGY-1 for IMGs and AMGs across the medical specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…For physicians who completed third medical training, but now wish to do their residency training in a new country, working as a scribe may have additional value. Scribing will familiarize those physicians with norms of that country's healthcare system (including the electronic health record) [9]. It will also provide opportunities to demonstrate their abilities and build relationships with clinicians, which in turn may provide opportunities to attain strong recommendation letters for applying to residency programs.…”
Section: Scribing and International Medical Graduatesmentioning
confidence: 99%
“…For physicians who completed third medical training, but now wish to do their residency training in a new country, working as a scribe may have additional value. Scribing will familiarize those physicians with norms of that country's healthcare system (including the electronic health record) [9]. It will also provide opportunities to demonstrate their abilities and build relationships with clinicians, which in turn may provide opportunities to attain strong recommendation letters for applying to residency programs.…”
Section: Scribing and International Medical Graduatesmentioning
confidence: 99%
“…Previous studies have demonstrated that international graduates, who make valuable contributions to the diversity and allocation of the physician workforce,31 may have unique learning needs related to communication, performing procedures,32 passing certifying examinations33 and adjusting to the transition to residency 34 35. Our data suggest that this cohort of paediatric residents may also benefit from targeted teaching, assessment and feedback related to ethics.…”
Section: Discussionmentioning
confidence: 62%
“…6,13,14 In addition, IMGs' own perceived underperformance in public health knowledge may suggest the need for more extensive linguistic and cultural orientation, as well as socioeconomic and health systems orientation, which may enhance IMGs' confidence. 7 Our experience suggests that IMGs have extremely heterogeneous cultural backgrounds, meaning that such orientation initiatives must be carefully tailored. Despite a rigorous interview process that also assesses language fluency, these results demonstrate the need for improvement in cultural acclimation.…”
Section: T a G G E D H 1 Discussionmentioning
confidence: 99%